Program Pemberdayaan Keluarga Dhuafa “Pengembangan Usaha Nasi Uduk Ibu Sedah” Warga Meruyung Depok - Hilmi, Muhammad Iqbal; Indira Dwi Kusumawardani; Regita Mutiara Winri; Mulkan Habibi (Yayasan Sagita Akademia Maju, 2025)
The empowerment program for the underprivileged family of “Ibu Sedah” in Meruyung, Depok, aims to enhance economic independence through an educational approach based on Muhammadiyah values. This program was implemented by students and lectures from the Communication Studies Program at Universitas Muhammadiyah Jakarta as part of the Al-Islam Kemuhammadiyahan course. The study adopted the Participatory Action Research (PAR) method to ensure active involvement of the beneficiares. The main subject of this program is Ibu Sedah, a 61st year old single mother who relies on an uncertain income from her nasi uduk business. Throgh surveys, interviews, and selection, the implementation team identified her primary needs. Activies in this program included fundraising, provision of business capital, as well as training in business management and educational motivation for her child. As a result, Ibu Sedah’s bussiness capacity improved and became more sustainable, while her child received educational support. This program highlights the importance of synergy between education, emprowerment, and community service in addressing poverty. The study serves as a reference for continuing similar programs with broader scope and sustainable approaches.